PENGEMBANGAN INSTRUMEN CABANG OLAHRAGA ATLETIK NOMOR TOLAK PELURU GAYA O’BRIEN PADA ATLET PUTRA PPLM PROVINSI RIAU - Ni Putu Nita Wijayanti; Slamet Slamet; Agus Wiranata (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2019)
The problem in this reserch originated from the observation to the field researchers who focus on the implementation of the recruitment of athletes PPLM Riau province, especially athletics shot put the number of instrument test is still common for a number in athletics. Based on the needs analysis, the researchers designed a development instrument of shot-put from physical, technical, tactical, and mental aspect. Research and development of the instrument using a qualitative approach and method development research Research & Development (R & D). The subjects in this research were four people who are all athletes PPLM Riau Province in 2016. Validity of test results using the product moment correlation can be described item development instruments, which have very high criteria consists of 4 items (36.36%) are weight, height, push-ups and standing, while 7 other test items have value product moment correlation with high criteria as much as 63.36%. For the results of reliability test r11 = 0.72 This means that the reliability of the instrument development that researchers in the category of sufficient reliability.